Screening Amazon rainforest plant extracts for antimicrobial activity: a 15-year commitment to the Brazilian biodiversity - Suffredini, Ivana Barbosa; Silva, Jefferson de Souza; Frana, Sergio Alexandre; Pinto, Katia Cristina; Bento, Keli Cristina Dias; Rudiger, Erika Costa; Belo, Paloma Kelly de Souza; de Arruda, José Rodrigo; Schulze, Juliana Paola; de Castilho, Adriana Lígia; Camargo, Livia Roberta Piedade; Paulino, Ricardo Olivieri; et al. (Frontiers in Antibiotics, 2023)
The need for new tools to fight infections constantly grows due to the possibilities of emerging diseases related to environmental changes, climatic catastrophes, microorganism resistance, and human and animal aging, leading to evident unbalance in the planet's health. Brazil contains the most significant portion of world biodiversity, a potential source of new antimicrobial natural products. Nonetheless, it has lately faced several threats against the environment, urging for rapid and precise research to prospect for antimicrobial activity. Plants from the Amazon and the Atlantic Rainforests are being collected and tested against several pathogenic microbes relevant to humans, animals, and the environment, and submitted to large-scale susceptibility assays, bioautography, and artemia salina toxicity assays. From the plants, 2,280 organic and aqueous extracts were obtained from different organs as leaves, barks, flowers, fruits, and seeds, and were submitted to a large-scale susceptibility screening assay against Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Streptococcus mutans, Streptococcus sanguinis, Escherichia coli, Pseudomonas aeruginosa, Candida albicans, Malassezia pachydermatis, Malassezia furfur, and Listeria monocytogenes. The selected extracts were submitted to antimicrobial susceptibility tests to obtain inhibition zone diameters and minimal bactericidal concentrations, bioautography, and to artemia salina toxicity assay, which resulted in 154 active extracts. Moreover, 111 out of 154 extracts were ranked based on scores established by the p-values and the mean rank differences in each set of test results. The final ranking gave the extracts a high priority to be further submitted to phytochemical studies using thin-layer chromatography techniques. The extracts obtained from plants belonging to Combretaceae, Connaraceae, Convolvulaceae, Fabaceae, Malpighiaceae, Moraceae, Piperaceae, Polygonaceae, and Salicaceae were selected as the most promising ones and support the identification of plant-based antimicrobial active compounds from the immense biodiversity of the Brazilian forests.